Two-Year Results of the 17-mm Avalus Aortic Valve in the PERIGON Japan Trial - Yaku, Hitoshi; Fujita, Tomoyuki; Nakajima, Hiroyuki; Fukumura, Yoshiaki; Gearhart, Elizabeth; Okita, Yutaka; Yamanaka, Katsuhiro; Yamaguchi, Atsushi; Komiya, Tatsuhiko; Murakami, Hirohisa; Zaikokuji, Kenta (Circulation Journal, 2021)
Background:The PERIcardial SurGical AOrtic Valve ReplacemeNt (PERIGON) Japan Trial was developed to assess the safety and effectiveness of the 17-mm Avalus bioprosthesis (Medtronic, Minneapolis, MN, USA) in patients undergoing surgical aortic valve replacement.Methods and Results:The primary endpoint in the trial was the percentage of patients achieving the composite of at least 1 class improvement in New York Heart Association (NYHA) functional class at 1 year compared with baseline and effective orifice area index (EOAI) of 0.6 cm2/m2or greater at 1-year after implantation, compared with a performance goal of 60%. The present study reports outcomes through 2 years. Eleven patients were implanted (10 [91%] female, median age 78.3 years). From baseline to 1 year, 10 subjects (91%) showed an improvement in NYHA classification. At 1 year, mean (±SD) EOAI was 0.82±0.17 cm2/m2, with 10 patients (91%) having an EOAI ≥0.6 cm2/m2. As such, 9 of 11 patients (82%) successfully met the primary endpoint. One death occurred between the 1- and 2-year follow-up visits, unrelated to the valve. There were no valve reinterventions, explants, or device deficiencies through 2 years.Conclusions:The PERIGON Japan Trial met its primary endpoint. Surgical implantation of the 17-mm Avalus aortic bioprosthesis can be performed with an acceptable incidence of device-related adverse events, and the valve performs effectively based on echocardiographic findings.